Optimal placement and sizing of STATCOM(s) for power system security improvement using MOPSO - Ismail, Bazilah; Abdul Wahab, Noor Izzri; Othman, Mohammad Lutfi; Mohd Radzi, Mohd Amran; Abdul Kahar, Nor Hidayah; Awalin, Lilik Jamilatul (IEEE, 2022)
The massive increase in both electrical power demand and the penetration level of renewable-based distributed generation at the distribution system has contributed to large amount of power flow in the grid's utility. As a consequence, part of the transmission networks is congested that led to unexpected outage and the entire grid is operated at the vulnerable condition. Static Synchronous Compensator (STATCOM) is one of the most effective ways to alleviate this problem. The benefits of introducing the STATCOM into the system can be further maximized with an appropriate location and size of the devices. In this work, the optimal number, location and sizing of STATCOM(s) are determined to reduce the real power loss and voltage deviation under several most severe N-1 and N-2 events. The most severe line outage events are determined using the proposed combine severity index (CI). The optimal location and sizing of STATCOM(s) in IEEE 30 bus test system are identified using multi-objective Particle Swarm Optimization algorithm (MOPSO).